Predicting traffic demand during hurricane evacuation using Real-time data from transportation systems and social media. (October 2021) - Roy, Kamol Chandra; Hasan, Samiul; Culotta, Aron; Eluru, Naveen
Highlights: Presents a data-driven approach for traffic prediction using real-time multi-source data from actual hurricanes. Shows the potential of social media and sensor data to predict traffic for a longer time horizon. Provides insights on how social media data can be synthesized with traffic sensor data. LSTM model outperforms baseline and existing machine learning models. Abstract: In recent times, hurricanes Matthew, Harvey, and Irma have disrupted the lives of millions of people across multiple states in the United States. Under hurricane evacuation, efficient traffic operations can maximize the use of transportation infrastructure, reducing evacuation time and stress due to massive congestion. Evacuation traffic prediction is critical to plan for effective traffic management strategies. However, due to the complex and dynamic nature of evacuation participation, predicting evacuation traffic demand long ahead of the actual evacuation is a very challenging task. Real-time information from various sources can significantly help us reliably predict evacuation demand. In this study, we use traffic sensor and Twitter data during hurricanes Matthew and Irma to predict traffic demand during evacuation for a longer forecasting horizon (greater than 1 h). We present a machine learning approach using Long-Short Term Memory Neural Networks (LSTM-NN), trained over real-world traffic data during hurricane evacuation (hurricanes Irma and Matthew) using different combinations of input features and forecast horizons. We compare our prediction results against a baseline prediction and existing machine learning models. Results show that the proposed model can predict traffic demand during evacuation well up to 24 h ahead. The proposed LSTM-NN model can significantly benefit future evacuation traffic management.